Modeling of kayak athletes competition activity - A.N. Kolumbet; L.Y. Dudorova; N.A. Babina; T.A. Bazulyuk; S.M. Chernovsky (Physical Education of Students)
Purpose: determination of correlations between parameters of special and technical fitness of kayak athletes on 500 meters’ distance. Material: in the research 29 elite athletes participated. We studied characteristics of athletes’ coordination structure in natural conditions and laboratory experiment. Results: significant influence of specific adaptive reactions on workability dynamic and sport results is noted. Constant reduction of power is connected with lactate, pyruvate and other under-oxidation products’ accumulation in athlete’s muscles. 500 meters’ distance passing in alternative regime of motor activity permits for athletes to achieve higher level of special workability. We studied four variants of 500 meters’ competition distance passing. Most of athletes pass this distance by third variant (46% of all tested athletes) 21% - by the first variant; 14% - by second variant and 19% by the forth. Conclusions: achievement of high sport result is facilitated by optimal structure of competition functioning, which corresponds to the following: speed power qualities and special endurance; individual features of athletes; specific of physical qualities’ manifestation, when passing definite distance.